Penghijauan dan Budidaya Lebah Klanceng untuk Lingkungan Lestari di Desa Sawocangkring - Bukti, Bukti; Mahardika, Agustina; Kurniawan, Novalia Ananda Putri; Asdianto, Vannesa Jeschilia; Suparman, Suparman (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
Reforestation and stingless bee (Trigona sp.) cultivation efforts serve not only as a conservative activity but also as an integrative strategy in addressing global environmental challenges. Reforestation can improve air quality, maintain soil fertility, and provide a sustainable food source for bees. Conversely, stingless bees contribute significantly to maintaining ecosystem sustainability through pollination processes that directly impact biodiversity and food security. This research encourages critical thinking on how the synergy between the two can be optimized into an environmentally-based circular economy model. The evaluation shows that the program's success is determined not only by the availability of green space, but also by awareness, active community participation, and innovation in cultivation management. Thus, the integration of reforestation and stingless bee cultivation can be a transformative solution in creating a sustainable environment while sustainably improving the socio- economic well-being of communities.